Quality of Life after Cerebral Venous Thrombosis - João Miguel Spínola Teixeira (2023)
Introduction and Objectives: Cerebral venous thrombosis (CVT) is a rare subtype of stroke, which affects mainly working-age adults: it is expected to affect the quality of life (QoL) due to symptoms that persist after the resolution of the event. The objective of this study is to study the QoL in post-CVT patients and to evaluate levels of anxiety, depression, and fatigue in post-CVT patients . Methods: Retrospective, single-center case-control study of patients admitted to the Neurology Department of CHUSJ with a diagnosis of CVT between January 2015 and December 2020, and non-CVT patients, with no known cerebrovascular disease, paired by age and gender. We applied questionnaires, validated to the Portuguese population to evaluate QoL, presence of depression/anxiety, and fatigue. Results: We included 13 cases and 13 controls; 76.9% of CVT patients were female. CVT patients showed lower evaluation in the Physical Health (CVT: 76.57 vs Control: 82.14, p=0.03), Psychological Health (CVT: 75 vs Control: 95.83, p<0.001), and Environment (CVT: 65.63 vs Control: 81.25, p=0.01) domains of the WHOQOL-Bref questionnaire. Discussion and Conclusion: CVT patients had significantly lower levels of physical and psychological health, as well as environmental health when compared to controls. Post-CVT management of the patients should also assess the effect that the residual symptoms have on the patient's life.